2022
DOI: 10.1093/jmammal/gyac053
|View full text |Cite
|
Sign up to set email alerts
|

Weather, fire, and density drive population dynamics of small mammals in the Brazilian Cerrado

Abstract: Understanding the relative importance of exogenous and endogenous factors in natural population dynamics has been a central question in ecology. However, until recently few studies used long-term data to assess factors driving small mammal abundance in Neotropical savannas. We used a 9-year data set, based on monthly captures, to understand the population dynamics of two scansorial small mammals inhabiting the Brazilian Cerrado: the semelparous gracile mouse opossum (Gracilinanus agilis), and the iteroparous l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 74 publications
0
1
0
Order By: Relevance
“…In the same study area, extreme temperatures also negatively affected small marsupials, with body mass of less than one kilogram (Ferreira et al 2016b). Rhipidomys mastacalis was also affected by temperature in the savanna region, but in an opposite way; a decrease in population growth rate was related to the number of very cold days in the previous year (Rossi & Leiner 2022).…”
Section: Modelmentioning
confidence: 86%
See 2 more Smart Citations
“…In the same study area, extreme temperatures also negatively affected small marsupials, with body mass of less than one kilogram (Ferreira et al 2016b). Rhipidomys mastacalis was also affected by temperature in the savanna region, but in an opposite way; a decrease in population growth rate was related to the number of very cold days in the previous year (Rossi & Leiner 2022).…”
Section: Modelmentioning
confidence: 86%
“…Small mammals, in general, have their dynamics dominated by a first-order mechanism, as is the case of rodents in dry and temperate regions (Berryman 2001, Merritt et al 2001, Lima et al 2006) and rodent and marsupials from tropical forests (Kajin et al 2008, Zangrandi 2011, Ferreira et al 2016a, Santos 2019). The only study that evaluated the feedback structure of a Rhipidomys population was conducted with Rhipidomys mastacalis for nine years in a tropical savanna ecoregion of Brazil (Rossi & Leiner 2022). Population growth rate was strongly determined by population density in the previous year, also indicating the occurrence of a first-order negative feedback, as in R. itoan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its data products have contributed to a rapid expansion of interdisciplinary research that relies on ecological knowledge and remote sensing data to describe a variety of patterns, including tracking loss of wetland habitat, detecting shifts in forest canopy composition, and monitoring shifts in phenological cycles (Vogelmann et al, 2016 ). Much of this work is forward‐looking, seeking to describe how natural systems evolve as climate change progresses and to construct relevant projections, but historical remote sensing data can also be used to add new dimensions to datasets lacking contemporaneous environmental measurements (e.g., Boult et al, 2018 ; Ndegwa Mundia & Murayama, 2009 ; Rossi & Leiner, 2022 ). Herein, we combine remote sensing and weather modeling data with previously collected demographic data to describe environmental factors influencing various components of population dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…These studies have identified both trophic interactions (food and/or predation) and seasonality as the main drivers of population dynamics of small mammals at higher-latitude temperate forests (Yoccoz et al 2001), deserts (Lima et al 2001), and grasslands (Aars & Ims 2002). Aside from these well-known studies, most studies evaluating small mammal population dynamics in tropical environments to date have been shortterm, which undermine the understanding of population patterns and processes (Cerqueira et al 1993, Barros et al 2015, but see da Rosa et al 2021, Rossi & Leiner 2022.…”
Section: Introductionmentioning
confidence: 99%